Preferential attachment and pattern formation in R&D networks: Plausible explanation or just a widespread myth? - Michael Fritsch; Muhamed Kudic (Friedrich Schiller University Jena, 2016)
The emergence and solidification of network patterns is typically explained by the preferential attachment rule. The underlying logic is that a small number of actors which are characterized by an above average degree attract links at a higher rate than others. We raise the question as to what extent the wide spread preferential attachment explanation holds true in the context of inventor networks. To shed some light on this issue we investigate co-patenting relationships among inventors in the field of laser technology in West Germany from 1961 to 2005. From a system perspective, the development of the inventor networks is in line with the pattern that is implied by the preferential attachment logic. However, we find high levels of fluidity of micro-level relationships that put the typical transaction cost and trust-based explanation of tie formation processes into question.
Keywords: O3; R1; L6; D2; D8; 330; preferential attachment; inventor networks; system stability; micro-level instability; laser industry